Link Adaptive One-Way Decode and Forward (DF) Relaying With Orthogonal Frequency Division Multiplexing (OFDM) - Yildirim, Mete; Ilhan, Haci (ELSEVIER SCIENCE BV, 2016)
In this paper, link adaptive one-way decode and forward (DF) relaying with Orthogonal Frequency Division Multiplexing (OFDM) is proposed. The relay, in the proposed system, adapts the power level of each sub-carrier according to power scaling factor which is obtained from source-relay and relay-destination fading parameters. The fading parameters are assumed to have Nakagami-m distribution. The link adaptive system is compared to the non-link adaptive one in multi-carrier transmission. To reach concrete results, the performance of the considered system is examined for various link adaptive factors, and it is shown that the proposed system achieves better bit error rate (BER) while reducing power consumption at relay. Besides, the proposed system combine the advantages of OFDM to the link adaptive relaying which reduces the complexity of equalizer at the receiver side and increases bandwidth efficiency. Simulation results are provided for various fading environments. The simulation shows that power scaling factor increases BER performance. This is also confirmed for various Nakagami-m channels. We further provide the analytic BER for the proposed system. (C) 2015 Elsevier Ltd. All rights reserved. Selection and Peer-review under responsibility of Conference Committee Members of International Semiconductor Science and Technology Conference 2015 (ISSTC 2015).
Keywords: Adaptive relaying; Decode and Forward; Relaying; OFDM; One-Way; WIRELESS NETWORKS; DIVERSITY; SYSTEM; Materials Science